Neopalimaia kupina . Neopalimaia kupina . Burning Bush . Неопалимая купина - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program about private farming in the Okulovsky region. interview with the workers of a selection station. Petersburg intelligentsia in the province. Problem of interrelations between city and village. Программа о частном фермерстве Окуловского района. Беседа с работниками селекционной станции. Петербургская интеллигенция в провинции. Проблема взаимоотношений города и деревни.